EUSÉBIO: LA CONSTRUCCIÓN DEL HÉROE EN LA PRENSA ESCRITA1 - Dr. João CANAVILHAS (Fonseca, Journal of Communication, 2023)
The translation of the football player Eusébio’s body to the National Pantheon was quite controversial in Portugal. The discussion was based on the correctness of having a football player buried in the Pantheon, a place reserved for national heroes. A hero is someone who lives most of the time as the others, but in certain conditions stands to a position of demigod (Rubio, 2001). From that moment, it earns the right to sit in a space reserved for all (pan) gods (theos). But how does a football player becomes a god, a sports hero? For his actions, obviously, but mainly by how the media tells the public his exploits.